PENERAPAN MEDIA PEMBELAJARAN BERBASIS GAMIFIKASI MENGGUNAKAN INTERAKTIF FLAT PANEL UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN DARAMISTA II - Winda Nuraisyah; Abu Bakar; Moh. Bakir; Malikatun Nabila; Siti Khotijah; Gusti Imani Ning Dias; Sholihatun Nafilah; Hilyatin Nafi’ah; Firdaus Firdaus (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Mathematics is an essential subject that plays an important role in developing students’ logical, systematic, critical, and creative thinking skills. However, in mathematics learning at the fourth grade of SDN Daramista II, several problems were found, such as low student interest in learning, limited participation in classroom activities, and the use of conventional teaching methods and media. These conditions have an impact on students’ low learning outcomes, particularly in the topic of rounding numbers. This study aims to analyze the implementation of gamification-based learning media using an Interactive Flat Panel to improve students’ mathematics learning outcomes. This research employed a qualitative approach with data collection techniques including observation, interviews, and documentation. The research subjects were the fourth-grade teacher and fourth-grade students at SDN Daramista II. The results showed that the implementation of gamification-based learning media through the Interactive Flat Panel increased student engagement, motivation, and participation during the learning process. Interactive features such as touch screens, digital quizzes, and educational games made learning more interesting and student-centered. In addition, the use of this media helped students understand the concept of rounding numbers more easily through repeated practice presented in a game-based format. Therefore, gamification-based learning media using an Interactive Flat Panel can serve as an innovative alternative to improve the quality of mathematics learning and students’ learning outcomes in elementary schools.